1992
DOI: 10.1007/bf00174853
|View full text |Cite
|
Sign up to set email alerts
|

The role of two Trichoderma reesei xylanases in the bleaching of pine kraft pulp

Abstract: The two major xylanases of Trichoderma reesei with different pI values and pH optima were compared for increasing the bleachability of pine kraft pulp. The efficiencies of the two enzymes acting on pulp substrate were very similar in hydrolysis yield, extraction kappa number or final brightness value. Only slight synergism between the two enzymes was observed in both hydrolysis and bleaching tests. The pH optimum of the pI 5.5 xylanase was similar in pulp treatment and in the hydrolysis of isolated substrates,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 6 publications
0
20
0
1
Order By: Relevance
“…Trichoderma consists of a number of economically important strains, valued for their biocontrol capabilities and ability to produce beneficial metabolites and enzymes (Papavizas, 1985 ;Ghisalberti & Sivasithamparam, 1991 ;Buchert et al, 1992 ;Schirmbock et al, 1994). In contrast to their usefulness to industry, however, there have also been reports of pathogenic strains that pose a threat to both horticulture and human health (Loeppke et al, 1983 ;Seaby, 1987 ;Menzies, 1993).…”
mentioning
confidence: 99%
“…Trichoderma consists of a number of economically important strains, valued for their biocontrol capabilities and ability to produce beneficial metabolites and enzymes (Papavizas, 1985 ;Ghisalberti & Sivasithamparam, 1991 ;Buchert et al, 1992 ;Schirmbock et al, 1994). In contrast to their usefulness to industry, however, there have also been reports of pathogenic strains that pose a threat to both horticulture and human health (Loeppke et al, 1983 ;Seaby, 1987 ;Menzies, 1993).…”
mentioning
confidence: 99%
“…The bleachability varied considerably depending on the origin of the enzyme and the type of the pulp. The mannanase purified from T. reesei was most effective in increasing the brightness of the pulps Based on data from Buchert, 1993;Buchert et al, 1992aBuchert et al, , 1992bClark et al, 1990;Clark et al, 1991. Original kappa number 34.4. Enzyme doses: xylanase 100 nKat g −1 , mannanase 500 nKat g −1 .…”
Section: A Impact Of Different Hemicellulase Enzymes In Bleachingmentioning
confidence: 97%
“…Pulpzyme HA (Novo Nordisk A/S) produced by T. reesei was the first commercially available xylanase to be used in the biobleaching of wood pulps and was capable of a 20% decrease in kappa number for oxygen-delignified birch kraftpulp (Ziaie-Shirkolaee et al 2008).The two major xylanases of T. reesei were ever compared for increasing the bleachability of pine kraft pulp, and the result suggested that the pI 9.0 xylanase act better on the pulp than the pI 5.5 xylanase (Buchert et al 1992). …”
Section: Introductionmentioning
confidence: 97%